Scoping Recreational Disturbance of Shorebirds to Inform the Agenda for Research and Management in Tropical Asia - Sumudu Marasinghe; Greg D. Simpson; David Newsome; Priyan Perera (Tropical Life Sciences Research, 2020)
In addition to scoping the impacts of the four most reported sources of recreational disturbance on shorebirds, this study also advances the concept of Tropical Asia (TA) to collectively describe tourist destinations in the ecologically and geopolitically diverse part of the planet that incorporates the tourism megaregion of South and Southeast Asia. At a time of growing global concern about the rapid decline of shorebird populations, many governments in TA are embracing and capitalising on the exponential growth in demand for coastal recreation and tourism across the region. This political response is partly driven by efforts to deliver economic development, aligned to the United Nations Sustainable Development Goals, in order to secure the livelihoods of people living in less developed coastal areas. However, the rapid increase in visitor numbers and the development of infrastructure to support the booming demand for coastal tourism destinations in TA are further exacerbating the pressures on shorebird populations across the region. Despite these growing pressures and the wealth of research reporting on shorebird populations across the Asian flyways, this scoping study identified surprisingly little research that reports on the recreational disturbance (RD) of shorebirds in TA. While undertaken to inform future research, this study also provides a synthesis of management strategies reported in the global literature into a set of management recommendations for coastal destinations in TA.